2021
DOI: 10.3389/fmicb.2021.676249
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Genetic Profiles of Vibrio vulnificus and Vibrio parahaemolyticus Isolated From the Maryland Coastal Bays, United States

Abstract: Vibrio vulnificus and V. parahaemolyticus, found naturally in marine and estuarine environments, are the leading cause of seafood associated gastrointestinal illness and death. Consumption of improperly cooked crabs and handling of live crabs are potential routes of exposure to pathogenic bacteria such as V. vulnificus and V. parahaemolyticus. Little information is available on serotype genetic and antimicrobial profiles of V. vulnificus and V. parahaemolyticus recovered from Maryland estuaries. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…are common causative agents of foodborne related infection in humans arising from contaminated water, undercooked or raw seafood consumption 2 . The common symptom of Vibrio infection is gastroenteritis and diarrhea which may sometimes be associated with virulence factors like shiga-like cytotoxin, toxin-coregulated pilus, cytotoxins, siderophores, hemolysins, proteases and heat-stable enterotoxin 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are common causative agents of foodborne related infection in humans arising from contaminated water, undercooked or raw seafood consumption 2 . The common symptom of Vibrio infection is gastroenteritis and diarrhea which may sometimes be associated with virulence factors like shiga-like cytotoxin, toxin-coregulated pilus, cytotoxins, siderophores, hemolysins, proteases and heat-stable enterotoxin 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio infections are commonly treated with tetracyclines, third-generation cephalosporin, fluoroquinolone, trimethoprim-sulfamethoxazole as well as aminoglycoside. Tetracyclines and fluoroquinolones are mostly used in protracted or severe cases of Vibrio illnesses as they are known to be associated with lesser mortality rates 4 . However, in recent decades, many bacteria including Vibrio have emerged with unprecedented resistance to many antimicrobials owing to abusive use in agricultural and human systems 9 .…”
Section: Introductionmentioning
confidence: 99%
“…streptomycin, neomycin and amikacin), proving the presence of plasmid born integrons which are the principle genetic materials of horizontal gene transfer (Manjusha & Sarita, 2011). Silva et al (2021) reported that V. vulnificus and V. parahaemolyticus isolated from the coastal bay in the USA expressed the highest resistance to cephalothins, which is one of the prescribed antimicrobials for vibriosis. Subsequently, they were resistant to cefoxitin, ceftazidime, ceftriaxone, cefotaxime, cefepime, meropenem and amikacin.…”
Section: Coastal Environmentsmentioning
confidence: 99%
“…The main clinical symptoms were severe gastroenteritis, wound infection, cellulitis and highly fatal septicemia [3] . In particular, individuals suffering from liver disease, cancer and immunocompromised individuals are more likely to develop fatal wound infection and primary sepsis once they are infected with V. vulnificus [4] . Patients with V. vulnificus infection tend to have a rapidly progressive clinical course, with more than 50% of patients dying within 48 hours of hospitalization [5] .…”
Section: Introductionmentioning
confidence: 99%